Factors affecting depression and suicidal tendency among the students for the educational process - Md Mehdi Rahman; Muhammad Al Amin (Journal of Social, Humanity, and Education, 2023)
Purpose: This study aims to identify factors that contribute to depression and increase suicidal ideation in students to measure the types of depression among the students. To know the extent of depression they suffered and identify the factors that stimulate suicide. Research methodology: The study wants to assess the factors that affect depression and suicidal tendencies among the students of Shahjalal University of Science and Technology and MC College, Sylhet. For collecting data, and questionnaire method was followed. The researcher selected 50 samples from both of these institutions. In this study, a mixed research approach has been followed. Results: The study disclosed that among the respondents, 90% had an idea about depression, and 90% got depression once in their lifetime. They suffered from major depressive disorder, bipolar disorder, premenstrual dysphoric disorder, etc. and suffered from bipolar disorder. Depression has an adverse effect on student's academic life. Besides, 72% said that they need more consciousness about their depression. The study also revealed that 8% are addicted to drugs and alcohol. The study further revealed that 64% thought the severity of depression could lead someone to suicide, and 28% said that they thought about suicide during their depression period. Limitations: The respondents wanted to keep the truth private in some cases. The researcher may have failed to collect the pros and cons of this issue. Contribution: Shahjalal University of Science and Technology and MC College, Bangladesh.